From Audience to Community: The Role of the Affective Factors and the Relationship between Audience and Newspaper Staff in the Process of its Successful Transformation towards Digital Presence - Smolak-Lozano, Emilia (Sociedad de la Información, 2013)
The main purpose of this work is to examine the role of engaged and loyal audience who maintain strong and close relationships with journalists in saving the medium and transforming its model. The work will demonstrate the role of Social Media and Social Media Research tools in cultivating and measuring affective elements of the audiences such as: engagement, interactivity, loyalty and trust. The conclusions will serve as the recommendation points for those media that undergone crisis currently and for those who are looking to modify and foment its audience model. The methodology applied in the study is based on the case study method and will apply Social Media Research in order to indicate the level of affective elements of the relationships between audience and journalists and the roles of both parties in structuring the bonds in the digital sphere.
Keywords: Redes sociales en Internet; Social media; Comunicación 2.0; Audience community; Press campaign; Digital transformation